Strength Properties of Concrete Using Marble Dust Powder - A. Dhanalakshmi; M. Shahul Hameed (East Asian Journal of Multidisciplinary Research, 2022)
Construction expenses have mostly grown unaffordable in recent years. Civil engineering institutes and stakeholders throughout the world have worked to develop recyclable and resource-saving concrete for building applications in order to reduce these expenses. The majority of environmental issues arise from the disposal of trash in areas where marble sculpting takes place. The marble stone slurry generates both stone slurry and solid wastes, and with the massive discharge of marble trash locally, emphasis has been focused on the utilisation of waste material. This study looked into the use of marble dust powder in concrete, with varied percentages of marble dust (0%, 5%, 10%, 15% & 20%) replaced by sharp sand in M20 grade concrete mixes, while the water cement ratio was kept constant at 0.45. The compressive and split tensile strength of the concrete were evaluated after 7 and 28 days of curing time to determine its quality, performance, and dependability. The laboratory findings revealed that replacing marble dust powder with cement boosted concrete strength by up to 10% in terms of compressive load resistance and tensile strength.